The Phenomenon of Psychosomatic Disorders Among Students at Al Kamal Islamic Boarding School, Tambaksari Subdistrict, Kuwarasan District, Kebumen - Rahmatullah, Azam Syukur; Kencono, Dewi Sekar; Putro, Khamim Zarkasyi (Jurnal Pengabdian Masyarakat Bangsa, 2024)
Islamic boarding schools are educational institutions aimed at providing teachings and understanding of Islamic religion. The life within a boarding school differs greatly from the outside world, which can be shocking for new students. When new students enter a boarding school, they undergo a drastic transition from a free life to a life full of rules. This drastic change often causes many students to feel uncomfortable and experience stress. The stress experienced by students can lead to problems such as anxiety, inability to concentrate during lessons, and psychosomatic disorders. Psychosomatic disorders have also occurred at Al Kamal Islamic Boarding School in Tambaksari, Kuwarasan District, Kebumen. The phenomenon of psychosomatic disorders at Al Kamal Islamic Boarding School has been experienced by several students, showing symptoms such as dizziness, nausea, vomiting, and unexplained pain. These psychosomatic disorders can be addressed through relaxation programs for students at the boarding school. This relaxation program aims to provide education and socialization about psychosomatic disorders, including their causes, symptoms, and ways to overcome them. After receiving education and socialization at Al Kamal Islamic Boarding School, students have knowledge about psychosomatic disorders and how to overcome them. Students also engage in relaxation activities to prevent and minimize psychosomatic disorders.